A Methodology to Introduce Sustainable Development Goals in Engineering Degrees by Means of Multidisciplinary Projects - Isidro Calvo; Edorta Carrascal; José Manuel González; Aintzane Armentia; José Miguel Gil-García; Oscar Barambones; Xabier Basogain; Inmaculada Tazo-Herran; Estibaliz Apiñaniz (MDPI AG, 2024)
The sustainable development goals (SDGs) reflect the relevance that sustainability is gaining in our societies. Including sustainability-related topics in university curricula requires the revision of the contents, teaching/learning strategies and assessment techniques. Although engineering degrees are starting to introduce them, it may become complex to design significant educational experiences. This partly comes from the fact that sustainability is a highly multidisciplinary issue but, currently, the knowledge is compartmentalised into subjects. In this challenging scenario, concrete activities are required for students to better internalise sustainability issues. This work aims to present a methodology that guides academic staff to materialise the design of sustainability-related multidisciplinary activities. Since the designers of new activities may benefit from knowledge of similar experiences, this article describes one implementation throughout eight subjects within the Bachelor's degree on Industrial Electronics and Automation Engineering at UPV/EHU. The analysis and optimisation of the thermal comfort and energy consumption in the Faculty building became the common thread to design an educational itinerary that covers several subjects along all academic years of the degree, making use of active methodologies. The problem is analysed for every subject from different perspectives. Two questionnaires, carried out before and after the activities, were used for analysing the perception of the students after the activities. Results proved that the multidisciplinary project raised awareness about the SDGs and allowed students to visualise how to apply the acquired skills in problems close to their experience. As a result, more students considered sustainability as a possible future professional activity.